2021
DOI: 10.1111/josi.12494
|View full text |Cite
|
Sign up to set email alerts
|

Peer and parental sources of influence regarding interracial and same‐race peer encounters

Abstract: This study investigated the socializing influence of peers and parents in interracial encounters by disentangling how children and adolescents consider peer and parent messages when predicting interracial and same‐race inclusion. Black and White children (9–14 years old, N = 246) predicted the likelihood of interracial and same‐race peer inclusion when peer and parent sources of influence were present and provided justifications for their expectations. Results revealed that, while participants predicted inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
(143 reference statements)
0
6
0
Order By: Relevance
“…They both introduce new ideas and conceptualization to the broader ERS literature. In the first article in this section, Burkholder et al (2021) present an empirical investigation of how children and adolescents weigh peer and parental influences when making interracial and same-race peer inclusion decisions. Using the social reasoning developmental (SRD) model, the authors found that in general children were less optimistic about peer encounters involving parental sources of influence than peer sources of influence.…”
Section: Peers and Friendshipsmentioning
confidence: 99%
“…They both introduce new ideas and conceptualization to the broader ERS literature. In the first article in this section, Burkholder et al (2021) present an empirical investigation of how children and adolescents weigh peer and parental influences when making interracial and same-race peer inclusion decisions. Using the social reasoning developmental (SRD) model, the authors found that in general children were less optimistic about peer encounters involving parental sources of influence than peer sources of influence.…”
Section: Peers and Friendshipsmentioning
confidence: 99%
“…Prior research investigating children’s and adolescents’ perceptions of parents’ attitudes indicated that youth often perceive ingroup peer preferences from parents (Burkholder et al, 2021; Hitti et al, 2020; Killen et al, 2002). In this study addressing what parents think directly, clear patterns of ingroup preference did emerge.…”
Section: Discussionmentioning
confidence: 99%
“…Based on both SIT (Hogg, 2016; Tajfel & Turner, 1979) and the integrative stereotyping framework (Abele et al, 2021), we expected parents to be most comfortable with peers who shared all of their child’s gender, race, and social class group memberships, and to describe them as similar to their child and positively in terms of “getting along” (e.g., kind; Burkholder et al, 2021; Grütter et al, 2021; Killen et al, 2002). In other words, if children’s and adolescents’ perceptions of parents’ attitudes investigated in prior research are in fact correct, then parents in this study should report the most comfort with peers reflecting their children’s ingroups (the more ingroups the better), and they should explain those decisions by describing those peers as similar to their child (per SIT) and likely to “get along” (per the integrative stereotyping framework).…”
Section: Youth Perceptions Of Parental Comfort With Intergroup Peer I...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ethnographic research reveals that adolescents and young adults engage in meaningful conversations about their heritage or ethnic-racial identity development, racial inequality, and discrimination with their friends and peers (Moffitt & Syed, 2021 ; Syed & Juan, 2012 ). Further, peers play a role in the transmission of culture and in youth exploration and navigation of what it means to be a member of a particular ethnic, racial, or cultural group (Wang & Lin, 2023 ), as well as in the promotion of openness to cultural diversity and intergroup peer inclusion (Burkholder et al, 2021 ; Killen et al, 2022 ). Social network-informed studies provide additional evidence for peers playing a vital role in cultural socialization.…”
Section: Introductionmentioning
confidence: 99%